Village Digital Spaces and Generational Politics: The Challenge of Inclusive Innovation in Rural Indonesia - 'Ulya, Saida; Sutrisno, Sutrisno (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The digital transformation of rural areas presents both opportunities and challenges for youth, particularly through the development of Village Digital Community Spaces (RKDD). This study explores how RKDD can be optimized as an inclusive and dynamic platform to foster youth innovation amidst the socio-cultural dynamics of village life. Conducted in Polorejo Village, which hosts an active yet under-resourced RKDD, this research employs a qualitative phenomenological approach to investigate young people’s lived experiences in engaging with digital spaces. Data were collected through semi-structured interviews, participatory observation, and documentation, and analyzed using open coding, thematic categorization, and verification. Findings reveal that while the RKDD provides basic training in areas such as graphic design and video editing—boosting self-confidence among youth—barriers persist in terms of advanced skills and program sustainability. Structural constraints, including top-down governance, hierarchical social norms, and inadequate infrastructure, often hinder the realization of youth-driven ideas. This study argues that strengthening RKDD as an innovation incubator requires not only technological infrastructure but also context-sensitive social adoption, sustained mentoring, cross-sector collaboration, and affirmative policies. Theoretically, it contributes to a broader socio-cultural understanding of rural digital transformation; practically, it advocates for participatory and intergenerational development planning in building inclusive and sustainable village innovation ecosystems.